The 3-methyl-4-nitrophenol (PNMC) compromises airway epithelial barrier function. (15th February 2018) - An, Yun-Fang; Geng, Xiao-Rui; Mo, Li-Hua; Liu, Jiang-Qi; Yang, Li-Teng; Zhang, Xiao-Wen; Liu, Zhi-Gang; Zhao, Chang-Qing; Yang, Ping-Chang
Highlights: Exposure of mice to 4-nitro-m-cresol (PNMC) induced nasal epithelial cell apoptosis. Exposure of mice to PNMC increased the permeability of the nasal epithelial barrier. PNMC increased casp8 and casp3 activities in nasal epithelial cells. Exposure to PNMC up regulated Fas and FasL expression in airway epithelial cells. Inhibition of caspase abolished the PNMC-induced airway epithelial barrier dysfunction. Abstract: Background and aims: It is recognized that the air pollution is associated with the pathogenesis of airway diseases. This study aims to elucidate the role of the 3-methyl-4-nitrophenol (PNMC), one of the components of diesel-exhaust particles, in compromising the airway epithelial barrier integrity. Methods: A549 cells, an airway epithelial cell line, were cultured to monolayers to be used as an in vitro epithelial barrier model. BALB/c mice were treated with nasal drops containing PNMC to test the effects of PNMC on alternating the airway epithelial barrier functions. Results: Exposure of mice to PNMC induced nasal epithelial cell apoptosis and increased the permeability of the nasal epithelial barrier. PNMC increased casp8 and casp3 activities in nasal epithelial cells. Exposure to PNMC up regulated Fas and FasL expression in airway epithelial cells. Inhibition of caspase abolished the PNMC-induced airway epithelial barrier dysfunction. Conclusion: Exposure of airway mucosa to PNMC induces epithelial cell apoptosis and compromises the epithelial barrier function, which can be prevented by the inhibition of caspases.